Corporate Profits and the Risk of Entry - Stonebraker, Robert J. (The Review of Economics and Statistics, 1976)
ECONOMISTS have recently begun to assess the quantitative effect of on corporate rates of return. Several studies have analyzed the relation between the profitability of large firms and the amounts of faced by large firms.' But none has yet considered that the profitability of large firms might be related to the amounts of faced by smaller, fringe firms within their respective industries. Most occurs on a small scale and entrepreneurs are likely to estimate the of entering an industry on the basis of the performance of existing small firms. If these small firms fail or are unable to consistently earn a normal rate of return, potential competitors may regard as risky. The greater is this risk, ceteris paribus, the less likely new firms will be to enter. In this sense, the faced by small firms acts as an barrier enabling large firms to earn excess profits without attracting new competitors. Alternatively, can be thought of as the vehicle through which barriers work. For example, where significant scale economies exist, the of entering the industry is likely to be high and, therefore, excess profits of existing large firms will be protected from new competition. Many of the characteristics that traditionally have been termed barriers can be interpreted as factors increasing the amount of faced by potential competitors. Section I of this paper develops a measure of entry risk and section II incorporates it into a simple theoretical model of large-firm profit rates. Section III discusses the construction of variables and the selection of data for empirical estimation of the model, and section IV presents the statistical results. Finally, in section V, a model explaining on the basis of such conventional barriers as economies of scale, advertising, and research and development expenditures is developed and tested. The conclusions and implications of the study are summarized in section VI.